Factors affecting organizational effectiveness in independent hotels – The case of Iran. (March 2021) - Nazarian, Alireza; Atkinson, Peter; Foroudi, Pantea; Edirisinghe, Dilini
Abstract: Because of an increasingly competitive environment managers of independent hotels need to enhance organizational effectiveness. Therefore, it is crucial to understand what factors affect effectiveness. To help achieve this, our study tests if transformational, transactional and laissez-faire leadership-styles, could indirectly influence organizational effectiveness through market and adhocracy organizational culture. Iran was chosen because it is a developing country with a growing tourist industry that has been under much restriction since the revolution. Survey data were gathered from managers of independent hotels in Iran and 340 questionnaires were returned out of 1050 distributed and examined using structural equation modelling. Our findings show that the transformational leadership-style has an indirect relationship with organizational effectiveness through the market and adhocracy culture types. However, transactional leadership has an indirect relationship with organizational effectiveness only through the market-culture type and laissez-faire only through the adhocracy-culture type. This paper adds to the body of literature on the application of the full range leadership theory, which was developed in the West, to other regional contexts as well as a fresh look into the influence of these leadership styles on other factors including organizational culture and organizational effectiveness. It also adds to the literature of independent hotels, which are an important yet under-researched part of the hospitality industry.